Identifikasi Metabolit Sekunder dan Aktivitas Antibakteri Ekstrak Daun Sungkai (Peronema canescens JACK.) terhadap Beberapa Bakteri Patogen - Arsyik Ibrahim; Hadi Kuncoro (Journal of Tropical Pharmacy and Chemistry, 2012)
A research which identification of secondary metabolites and antibacterial activity test from methanol exstract of leaf Sungkai (Peronema canencens Jack) to several pathogens bacterial, which aims to identification of secondary methabolites and determine the antibacterial activity from crude methanol extract of leaf Sungkai (P. canencens Jack). against Streptococcus mutans, Salmonella thyposa, Bacillus subtilis and Staphylococcus aureus bacteria. Material test obtained by maceration with methanol, then tested for activity. Minimum Inhibition Concentration (MIC) value extract was determined by liquid dilution and the followed by scratches on solid media method.  Minimum Kill Concentration (KBM) value extracts was determined by agar diffusion method with using paper disks.The results secondary metabolite identify form extracts of leaves P. canencens obtainable derived alkaloid, terpenoids - steroids, flavonoids, and tannin compounds. Methanol extract have the antibacterial activity. Minimum Inhibition Concentration (MIC) value of extract is concentration of 20% for bacteria S. mutans, S.thiposa and S.aureus, while for the B. subtilis is konsentration of 15%. Minimum Kill Concentration (KBM) values exstract at a concentration of 5% effective at killing S. mutans and S. thyposa bacteria, while the concentration of 1% effective to bacteria B.subtilis and S.aureus.